Chromatography refolding of recombinant alpha-fetoprotein for high refolding productivity and intensified bioprocessing - Chen, Yu (2011)
Alpha-fetoprotein (AFP) is a commercially valuable biopharmaceutical candidate for autoimmune indications. Transgenically-derived recombinant AFP has recently successfully completed a Phase Two clinical trial study for rheumatoid arthritis indications at Merrimack Pharmaceuticals (Cambridge, MA, USA). The launch of this protein on market shelves in the future will subsequently demand cheaper second-generation product when product patent expires, thus necessitating new processes that can reduce product cost. The production of AFP as inclusion bodies (IBs) in Escherichia coli (E. coli) is advantageous for process-scale commercial manufacture due to speed, simplicity and cost reasons but conversion of the inactive protein aggregate into biologically active protein requires an efficient refolding step. The use of dilution refolding in previously reported recombinant human AFP (rhAFP) laboratory processes has resulted in low refolding yields, which negatively impacts the overall process yield and productivity. A superior refolding and bioprocessing route is clearly needed to facilitate efficient and rapid product delivery to market, if a commercial process for rhAFP is to be possible.